2017
DOI: 10.1002/ejic.201700556
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted and Lewis Base Behavior of Sodium Amidotrihydridoborate (NaNH2BH3)

Abstract: Abstract:The reactivity of sodium amidoborane (NaNH 2 BH 3 ) as a Brønsted and Lewis base was studied systematically. The [NH 2 BH 3 ] -anion can act as a proton acceptor or a hydride donor in different types of reactions. In reactions with very weak Brønsted acids such as cyclopentadiene, ammonia, and pyrazole, the [NH 2 BH 3 ] -anion acts as a proton acceptor through the lone pair on N. The reactions of [NH 2 BH 3 ] -with stronger Brøn-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Complex mixture A, Complex mixture B, Mixture C, Complex mixture D.The diffraction patterns of sodium imidazolate and cobalt metaphosphate are in good agreement with published literature of Chen et al21 and Ahn et al,22 respectively. The complex mixture D consists of cobalt metaphosphate, Co(PO 3 ) 2 , sodium imidazolate, C 3 H 3 N 2 Na, cobalt sulfate hexahydrate, [Co(H 2 O) 6 ]SO 4 , and imidazole, C 3 H 4 N 2 .…”
supporting
confidence: 89%
“…Complex mixture A, Complex mixture B, Mixture C, Complex mixture D.The diffraction patterns of sodium imidazolate and cobalt metaphosphate are in good agreement with published literature of Chen et al21 and Ahn et al,22 respectively. The complex mixture D consists of cobalt metaphosphate, Co(PO 3 ) 2 , sodium imidazolate, C 3 H 3 N 2 Na, cobalt sulfate hexahydrate, [Co(H 2 O) 6 ]SO 4 , and imidazole, C 3 H 4 N 2 .…”
supporting
confidence: 89%
“…Thus it is somewhat unsurprising that little research effort has been invested into understanding this reaction . Generally, there are four fates of the newly formed B−H−B unit (Figure , i – iv ): ( i ) the bridging hydrogen bond is cleaved and the hydride transfers from one boron atom to the other;, This constitutes a hydride transfer, a type of reaction that will not be discussed at length herein; ( ii ) the newly formed B−H−B bond reversibly reverts back to the starting materials; ( iii ) the formed B−H−B bond is maintained in the final product in the presence of a suitable environment; and ( iv ) the formed B−H−B bond is stabilized by the subsequent formation of a new chemical bond to give a cyclic molecule ,…”
Section: The Nucleophilicity Of the B−h Bonding Pair Electronsmentioning
confidence: 99%
“…Based on this renewed interest, the basic chemistry of these species has been developed further. A recent investigation indicated that the reaction of NaNH 2 BH 3 with NH 3 ⋅BH 3 or THF⋅BH 3 produces different products (Scheme ) ,. When NaNH 2 BH 3 was reacted with NH 3 ⋅BH 3 in THF under reflux, Na[NH 2 (BH 3 ) 2 ] was formed as the major product, with polyaminoborane [NH 2 BH 2 ] n , and NaBH 4 as minor products (Scheme A).…”
Section: The Nucleophilicity Of the B−h Bonding Pair Electronsmentioning
confidence: 99%
“…Boron compounds are of interest because of their unique properties as Lewis acids [1][2][3][4], hydrogen storage compounds [5][6][7][8], and as catalysts in chemical reactions [9,10]. Also, because of the electron deficiency of the B atom, boron compounds are used as strong anion receptors [11,12].…”
Section: Introductionmentioning
confidence: 99%